Factors influencing early disc height loss following lateral lumbar interbody fusion - Kaliya-Perumal, Arun-Kumar (2021)
Study Design: Retrospective radiological analysis. Purpose: To analyze the factors influencing early disc height loss following lateral lumbar interbody fusion (LLIF). Overview of Literature: Postoperative disc height loss can occur naturally as a result of mechanical loading. This phenomenon is enabled by the yielding of the polyaxial screw heads and settling of the cage to the endplates. When coupled with cage subsidence, there can be significant reduction in the foraminal space which ultimately compromises the indirect decompression achieved by LLIF. Methods: Seventy-two cage levels in 37 patients aged 62±10.2 years who underwent single or multilevel LLIF for degenerative spinal conditions were selected. Their preoperative and postoperative follow-up radiographs were used to measure the anterior disc height (ADH), posterior disc height (PDH), mean disc height (MDH), disc space angle (DSA), and segmental angle. Correlations between the loss of disc height and several factors, including age, construct length, preoperative lordosis, postoperative lordosis, disc height, cage dimensions, and cage position, were analyzed. Results: We found that the lateral interbody cages significantly increased ADH, PDH, MDH, and DSA after surgery (p <0.0001). However, there was a loss of disc height over time. All postoperative disc height parameters, especially the amount of increase in MDH (r =0.413, p <0.0001) after surgery, showed a significant positive association with early disc height loss. The levels demonstrating a significant (≥25%) height loss were those that exhibited a substantial height increase (128.3%, 4.6±3.0 to 10.5±5.6 mm) postoperatively. However, the levels that showed less than 25% height loss were those that exhibited, on average, only a 57.4% height increase post-operatively. Conclusions: The greater the postoperative increase in disc height, the greater the disc height loss throughout early follow-up. Therefore, achieving an optimal disc height rather than overcorrection is an important surgical strategy to adopt when performing LLIF.